2020
DOI: 10.1007/s40279-020-01268-x
|View full text |Cite
|
Sign up to set email alerts
|

Current Evidence of Measurement Properties of Physical Activity Questionnaires for Older Adults: An Updated Systematic Review

Abstract: Background Questionnaires provide valuable information about physical activity (PA) behaviors in older adults. Until now, no firm recommendations for the most qualified questionnaires for older adults have been provided. Objectives This review is an update of a previous systematic review, published in 2010, and aims to summarize, appraise and compare the measurement properties of all available self-administered questionnaires assessing PA in older adults. Methods We included the articles evaluated in the previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
57
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 159 publications
(231 reference statements)
2
57
1
2
Order By: Relevance
“…GPAQ uses a typical week to assess PA data; however, a typical week can be different in many European countries due to weather conditions yielding different PA levels. (iii) The season of the assessed PA was not taken into account, and therefore different results could be reported from studies since the EU has four seasons; (iv) even though the quality of each study was assessed, findings from studies of a lower quality were given no less importance than the other findings; (v) sample type might have a potential impact on the results of the study, since 13 out of 20 used convenience sampling; (vi) meta-analysis included only 17 studies, whereas the systematic review included 20 studies; (vii) coefficients of associations were reported whether or not they were significant or insignificant in initial studies, potentially leading to different results if only significant results were used; (viii) according to the PROSPERO register we left Eurobarometer out of the manuscript since we did not find any validation studies; (ix) this review includes studies from the UK, although at the time of publication, the UK is no longer a part of the EU; (x) although there exist other widely used PA questionnaires, targeting specific parts of the populations, such as Physical Activity Scale for the Elderly [ 85 ], we focused only on the questionnaires targeting the general adult population; and (xi) results of the present meta-analysis refers only to the adult population and are not necessarily valid in other populations such as the elderly, children and patients.…”
Section: Discussionmentioning
confidence: 99%
“…GPAQ uses a typical week to assess PA data; however, a typical week can be different in many European countries due to weather conditions yielding different PA levels. (iii) The season of the assessed PA was not taken into account, and therefore different results could be reported from studies since the EU has four seasons; (iv) even though the quality of each study was assessed, findings from studies of a lower quality were given no less importance than the other findings; (v) sample type might have a potential impact on the results of the study, since 13 out of 20 used convenience sampling; (vi) meta-analysis included only 17 studies, whereas the systematic review included 20 studies; (vii) coefficients of associations were reported whether or not they were significant or insignificant in initial studies, potentially leading to different results if only significant results were used; (viii) according to the PROSPERO register we left Eurobarometer out of the manuscript since we did not find any validation studies; (ix) this review includes studies from the UK, although at the time of publication, the UK is no longer a part of the EU; (x) although there exist other widely used PA questionnaires, targeting specific parts of the populations, such as Physical Activity Scale for the Elderly [ 85 ], we focused only on the questionnaires targeting the general adult population; and (xi) results of the present meta-analysis refers only to the adult population and are not necessarily valid in other populations such as the elderly, children and patients.…”
Section: Discussionmentioning
confidence: 99%
“…Other scales include the Community Health Activities Model Program for Seniors [ 71 ], General Practice Physical Activity Questionnaire [ 72 ], Modified Leisure Time Physical Activity Questionnaire [ 73 ], Stanford Brief Activity Survey [ 74 ], and Physical Activity and Sedentary Behavior Questionnaire (PASB) [ 73 ]. In a systematic review, most scales except for the PASE and PASB suffered from large measurement errors, low-quality evidence, and the lack of tests of reliability and construct validity [ 75 ]. Few of these scales were tested in individuals with cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the direct impact of the disease on the person can be assessed by means of the Arthritis Self-Efficacy Scale, Berg Balance Scale, Chronic Venous Insufficiency Questionnaire or, to evaluate the functional capacity of the patient, the Assessment of Motor and Process Skills or the Physical Activity Scale for the Elderly, among other instruments (see Table S4 ( Supplementary Materials )). Therefore, the application of a set of questionnaires with chosen criteria provides a comprehensive view of the patient’s health status and will facilitate a therapeutic approach [ 32 ]. The application time of the instrument must be regulated; instruments such as the Child Health Assessment Questionnaire, Assessment of Motor and Process Skills or Short Form-36 (30–40 min) ( Table S3 ( Supplementary Materials )) may be of excessive duration and can be difficult to integrate into an evaluation process within a clinical consultation.…”
Section: Discussionmentioning
confidence: 99%
“…The psychometric properties of the questionnaires are fundamental as they allow us to identify the validity and reliability to apply the best instrument on each occasion [ 33 ] ( Table S4 ( Supplementary Materials )). The highest test-retest reliability identified was in the Berg Balance Scale 0.99 [ 32 ] and the Chronic Venous Insufficiency Questionnaire 0.98 [ 34 ]. However, the lowest values were observed in the Assessment of Quality of Life Scale 0.78 [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation